Black Panther in exile : the Pete O'Neal story - Magnarella, Paul J. (University Press of Florida, 2020)
"This book tells the story of Pete O'Neal, one of the most influential members of the Black Panther Party, who now lives in exile in Tanzania-unable to return to the United States but refusing to renounce his past"--